2023
DOI: 10.3390/plants12030684
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wool Mulch on Plant Development in the Context of the Physical and Biological Conditions in Soil

Abstract: Mulching techniques can comprise a solution that better utilizes precipitation and irrigation water in such a manner that mitigates soil degradation and drought damage; however, there are still gaps in the literature with regard to the effect of the use of mulch materials on the development of plant–soil–microbe interactions. Waste fibers, as alternative biodegradable mulch materials, are becoming increasingly prominent. The effect of wool mulch (WM) on water use efficiency, with regard to pepper seedlings, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It's crucial to examine the pH needs of plants and pick mulch appropriately. Thick amounts of organic mulch may block gas exchange, reducing oxygen supply to roots and fostering anaerobic conditions (Juhos et al, 2023).…”
Section: Straw Strip Mulchingmentioning
confidence: 99%
“…It's crucial to examine the pH needs of plants and pick mulch appropriately. Thick amounts of organic mulch may block gas exchange, reducing oxygen supply to roots and fostering anaerobic conditions (Juhos et al, 2023).…”
Section: Straw Strip Mulchingmentioning
confidence: 99%
“…good moisture retention capacity (Juhos et al, 2023). Due to the slow degradation of wool pellet, the release of N is also slower, thus aiding NO 3 − uptake as it is not leached from the soil (Bradshaw & Hagen, 2022).…”
Section: Core Ideasmentioning
confidence: 99%
“…In recent times, the horticultural use of wool industry by‐products as organic fertilizers has become very popular (A. Abdallah, Ugolini, Baronti, Maienza, Camilli et al., 2019). Wool pellets are rich in nutrients, especially N, and have a good moisture retention capacity (Juhos et al., 2023). Due to the slow degradation of wool pellet, the release of N is also slower, thus aiding NO 3 − uptake as it is not leached from the soil (Bradshaw & Hagen, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of various studies have shown that the relative abundances of rhizosphere microbes change under mulch treatment. Juhos et al, 2023 found that straw mulch could improve microbiological parameters when compared to wool mulch [14]. Recent findings have shown that organic mulch helps regulate soil-microbial communities in tea and litchi [15,16].…”
Section: Introductionmentioning
confidence: 98%